2003
DOI: 10.1001/archinte.163.18.2230
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Long-term Cardiac Management After Major Vascular Surgery<subtitle>Role of β-Blocker Therapy, Clinical Characteristics, and Dobutamine Stress Echocardiography to Optimize Long-term Cardiac Management After Major Vascular Surgery</subtitle>

Abstract: Long-term beta-blocker use is associated with a reduction in the cardiac event rate, except for patients with 3 or more risk factors and positive findings on DSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Several studies have suggested that the extent of the wall-motion abnormality and/or wall-motion change at low ischemic thresholds, particularly at a heart rate of less than 60% of age-predicted maximum, 243,247 is especially important. These findings have been shown to be predictors of long-term 243,244,252,253 and short-term 254 outcomes.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have suggested that the extent of the wall-motion abnormality and/or wall-motion change at low ischemic thresholds, particularly at a heart rate of less than 60% of age-predicted maximum, 243,247 is especially important. These findings have been shown to be predictors of long-term 243,244,252,253 and short-term 254 outcomes.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 92%
“…89,248 In patients at low to intermediate clinical risk who are undergoing established and therapeutic beta blockade, DSE is unlikely to impact the early perioperative outcome 248 but contributes to the stratification of long-term cardiac risk. 253 Dobutamine stress magnetic resonance imaging has been used to identify myocardial ischemia in those not well suited for dobutamine stress transthoracic echocardiography. [255][256][257] In more than 500 patients across 6 studies, both the sensitivity and specificity of dobutamine stress magnetic resonance for appreciating 50% coronary arterial luminal narrowings have been demonstrated to range between 83% and 91%.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…Clearly, less-than-optimal medication was used in view of current guidelines on risk management for patients with manifestations of atherosclerosis. [14][15][16] Of course, better perioperative and postoperative management of risk factors could also improve the results of open aneurysm repair.…”
Section: No At Riskmentioning
confidence: 99%
“…Several studies have suggested that the extent of the wall-motion abnormality and/or wall-motion change at low ischemic thresholds, particularly at a heart rate of less than 60% of age-predicted maximum, 241,245 is especially important. These findings have been shown to be predictors of long-term 241,242,250,251 and short-term 252 outcomes.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 92%
“…88,246 In patients at low to intermediate clinical risk who are undergoing established and therapeutic beta blockade, DSE is unlikely to impact the early perioperative outcome 246 but contributes to the stratification of longterm cardiac risk. 251 Dobutamine stress magnetic resonance imaging has been used to identify myocardial ischemia in those not well suited for dobutamine stress transthoracic echocardiography. [253][254][255] In more than 500 patients across 6 studies, both the sensitivity and specificity of dobutamine stress magnetic resonance for appreciating 50% coronary arterial luminal narrowings have been demonstrated to range between 83% and 91%.…”
Section: Fleisher Et Al 2009 Accf/aha Perioperative Guidelines E195mentioning
confidence: 99%